[View of a Westman Island From Beach] - Streng, Evelyn Fiedler (1975)
Photograph of a Westman Island from a beach on Heimaey. The tall, brown and grassy, mountainous island is visible in the background surround the blue ocean. Brown and grey rocks cover the beach in the foreground. A line of brown rocks sit along the beach on the right edge of the photograph. A grey wall of clouds is visible in the background.